The Role of Digital Games in Children'S Life - Stajka B. Rajić; Alma Tasevska (University of Belgrade, Teacher Education Faculty, 2020)
Starting from the questions to what extent children use digital games and for what purposes as well as whether teachers play a role in the creation and presentation of different teaching content by using digital games, a survey was conducted with pupils of the third and fourth grades of primary school in the Republic of Serbia. The research involved three hundred and eight students from two private and four state primary schools. The results show that 100% of the respondents confirm that they play digital games, mostly for the purpose of entertainment and recreation, but also for understanding and observing a new educational content. The results of the survey also showed that there is a significant difference in the level of using digital games in public and private schools. Examining students' attitudes towards the use of digital games in teaching indicates that children are highly motivated to master educational content through digital games.